Prenatal sonographic diagnosis of limb body wall complex: A rare lethal fetal anomaly - Janet A Akinmoladun; Oluwasomidoyin Olukemi Bello (Sahel Medical Journal, 2019)
Limb-body wall complex (LBWC) is a rare fatal congenital malformation syndrome. We report a case of sonographically diagnosed LBWC at the gestational age of 28 weeks which was confirmed after delivery. The parents opted for termination of pregnancy. Physical examination postdelivery revealed a large abdominal and thoracic wall defect with the contents protruding outside the body without any covering membrane. The umbilical cord and the eviscerated urinary bladder arose from the midline. In addition, there was the absence of the right upper limb. The baby died few minutes after the delivery. Early antenatal sonological diagnosis is necessary so that the parents can make an informed decision on the options of continuation or termination of pregnancy. Therefore, expertise in prenatal detection of congenital anomalies is invaluable in antenatal care.